FROM COMMUNITY TO CLASSROOM: A PORTRAITURE STUDY OF SURVIVANCE AND COMMUNITY CULTURAL WEALTH AMONG NATIVE AMERICAN AND ALASKA NATIVE PRESERVICE TEACHERS AT A NATIVE AMERICAN SERVING NONTRIBAL INSTITUTION - Deswood, Kari L., author; Barone, Ryan, advisor; Bubar, Roe, committee member; Coffino, Kara, committee member; Lange, Alex, committee member (Colorado State University. Libraries, 2026)
Native American and Alaska Native students remain underrepresented in teacher education programs, emphasizing the need for research that centers their experiences. This study explored the lived experiences of Native American and Alaska Native preservice teachers enrolled at a Native American-Serving Nontribal Institution (NASNTI) in the Southwest. Guided by Tribal Critical Race Theory, Community Cultural Wealth, and Culturally Sustainable Revitalizing Pedagogy, this study also considered the research process and participant representation. Using the portraiture methodology, this study highlights participants’ stories to show how they navigate teacher education while honoring their families, communities, and tribal nations.Findings show that participants’ paths into and through teacher education are often nonlinear and influenced by relational responsibilities like parenting, community roles, and connections to their home communities. They relied on various forms of community cultural wealth, particularly familial, aspirational, and navigational capital, to persevere within institutional settings that do not always support Native students. While NASNTIs offer important access and opportunities, participants also noted tensions between institutional expectations and community commitments. Throughout their stories, participants expressed a strong desire to serve their communities as educators and to preserve Indigenous knowledge, language, and identity. This study adds to the literature by emphasizing the relational and community-centered aspects of Native teacher preparation and provides insights for programs aiming to better support Native American and Alaska Native preservice teachers.